The Efficiency of Operating Microscope Compared with Unaided Visual Examination, Conventional and Digital Intraoral Radiography for Proximal Caries Detection - Ilkay Peker; Meryem Toraman Alkurt; Oya Bala; Bulent Altunkaynak (Hindawi Limited, 2009)
Objective. The purpose of this study was to evaluate the efficiency of operating microscope compared with unaided visual examination, conventional and digital intraoral radiography for proximal caries detection. Materials and Methods. The study was based on 48 extracted human posterior permanent teeth. The teeth were examined with unaided visual examination, operating microscope, conventional bitewing and digital intraoral radiographs. Then, true caries depth was determined by histological examination. The extent of the carious lesions was assessed by three examiners independently. One way variance of analysis (ANOVA) and Scheffe test were performed for comparison of observers, and the diagnostic accuracies of all systems were assessed from the area under the ROC curve (𝐴𝑧). Results. Statistically significant difference was found between observers (𝑃<.01). There was a statistically significant difference between operating microscope-film radiography, operating microscope-RVG, unaided visual examination-film radiography, and unaided visual examination-RVG according to pairwise comparison (𝑃<.05). Conclusion. The efficiency of operating microscope was found statistically equal with unaided visual examination and lower than radiographic systems for proximal caries detection.